Young children's experiences of their hospitalisation for Cardiac surgery - Power, Nina Mary (My University, 2006)
The aim and objectives of this study were to explore, interpret and describe young children’s experiences of hospitalisation for cardiac surgery and to describe their parents’ opinions regarding significant changes in the children one month after discharge. A qualitative design, grounded in phenomenology was used. Semi-structured interviews were conducted with the children prior to discharge and with their parents one month later. The children’s interviews were augmented by drawings, which were used to keep the children focused and to highlight themes that were not identified from their verbal accounts of hospitalisation. The expertise of a clinical psychologist was sought for the analysis of the children’s drawings. The results of the analysis of the drawings supported the children’s verbal accounts of their experiences in hospital. Children’s interviews revealed that young children experience and cope with hospitalisation for cardiac surgery very differently. Parents’ presence, pain and boredom were dominant themes that emerged from the children’s interviews. Behavioural changes and emotional responses included withdrawal, tearfulness, disturbed sleep patterns, sadness, fear, anger and happiness. Parents’ interviews one month after discharge revealed a lack of communication between the nurses and the children. iv It is recommended that further research be conducted with older children to determine the effects of stringent visitation regulations followed in the paediatric intensive care setting.
Student no 9500767A Masters Report - School of Therapeutics
Keywords: children; hospital; clinical; psychologist; withdrawal